Pre-neoplastic epigenetic disruption of transcriptional enhancers in chronic inflammation - Aline Cristiane Planello; Rajat Singhania; Ken J. Kron; Swneke D. Bailey; David Roulois; Mathieu Lupien; Sérgio Roberto Peres Line; Ana Paula de Souza; Daniel D. De Carvalho (2016)
// Aline C. Planello 1,2,* , Rajat Singhania 1,* , Ken J. Kron 1 , Swneke D. Bailey 1 , David Roulois 1 , Mathieu Lupien 1,3 , Sérgio R. Peres Line 2 , Ana Paula de Souza 2 and Daniel D. De Carvalho 1,3 1 Princess Margaret Cancer Centre, University Health Network, Toronto, ON, Canada 2 Department of Morphology, Piracicaba Dental School, University of Campinas, Piracicaba, SP, Brazil 3 Department of Medical Biophysics, University of Toronto, Toronto, ON, Canada * These authors have contributed equally to this work Correspondence to: Daniel D. De Carvalho, email: // Ana Paula de Souza, email: // Keywords : DNA methylation, enhancers, chronic periodontitis, oral cavity squamous cell carcinoma Received : December 14, 2015 Accepted : February 09, 2016 Published : February 19, 2016 Abstract Chronic periodontitis (CP) is a chronic inflammatory disease independently associated with higher incidence of oral cavity squamous cell carcinoma (OSCC). However, the molecular mechanism responsible for this increased incidence is unknown. Here we profiled the DNA methylome of CP patients and healthy controls and compared to a large set of OSCC samples from TCGA. We observed a significant overlap between the altered DNA methylation patterns in CP and in OSCC, suggesting an emergence of a pre-neoplastic epigenome in CP. Remarkably, the hypermethylated CpGs in CP were significantly enriched for enhancer elements. This aberrant enhancer methylation is functional and able to disrupt enhancer activity by preventing the binding of chromatin looping factors. This study provides new insights on the molecular mechanisms linking chronic inflammation and tumor predisposition, highlighting the role of epigenetic disruption of transcriptional enhancers.